1998
DOI: 10.1002/hep.510280113
|View full text |Cite
|
Sign up to set email alerts
|

Allelic imbalance of insulin-like growth factor II gene expression in cancerous and precancerous lesions of the liver

Abstract: Allelic imbalance of the insulin-like growth factor II (IGF II) gene expression is often seen in hepatocellular carcinoma (HCC).Insulin-like growth factor II (IGF II) is a single-chain polypeptide that exerts its growth-stimulative effect through the IGF I receptor. The IGF II is speculated to serve as an autocrine growth factor in various cancers, because they often coexpress the IGF II and the IGF I receptor. [1][2][3][4] The IGF II gene expression is monoallelic in all the normal tissues other than the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Yamada et al 23 found the same insulinlike growth factor receptor II gene allelic loss in both dysplastic nodules and the adjacent cirrhotic tissue. The allelic imbalance of insulin-like growth factor II was also demonstrated by Aihara et al 24 in 3 of 7 dysplastic nodules.…”
supporting
confidence: 57%
“…Yamada et al 23 found the same insulinlike growth factor receptor II gene allelic loss in both dysplastic nodules and the adjacent cirrhotic tissue. The allelic imbalance of insulin-like growth factor II was also demonstrated by Aihara et al 24 in 3 of 7 dysplastic nodules.…”
supporting
confidence: 57%
“…Concerning insulin-like growth factor II, there have been reports that it was positive in 60% of HBsAg-positive HCCs, 25.6% of HBsAg-negative HCCs, and some benign neoplastic lesions, 38 and that its expression was enhanced in dysplastic nodules, but not in well-differentiated or moderately differentiated HCCs. 39 According to our results, the mean expression rate of insulin-like growth factor II was 0.76, and it was enhanced 2-fold or more in 1 patient, but reduced to 0.5 or less in 3 patients. Its expression rates in Cases 2 and 3, in whom HBsAg was positive, were 0.90 and 0.60, respectively, indicating no clear enhancement.…”
Section: Discussionmentioning
confidence: 87%
“…IGF-2 gene expression is controlled by mechanisms such as parental imprinting resulting in downregulation of one allele. In HCC, loss of heterozygosity and changes in the methylation patterns within the IGF-2 genes have been documented, and the perturbation of these control mechanisms seems to result in upregulation of IGF-2 expression from promoters characteristic of foetal development (Aihara et al, 1998). Moreover, differential usage of foetal and adult IGF-2 promoters was observed in premalignant proliferations present in HCV-related chronic liver disease (Tanaka et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, large proportions of the IGF-2-mRNA were found as splice forms characteristic for foetal tissues (Cariani et al, 1988). An allelic imbalance of IGF-2 gene expression correlating with the loss of maternal imprinting patterns was also considered to have a role in hepatocarcinogenesis (Aihara et al, 1998;Schwienbacher et al, 2000).…”
mentioning
confidence: 99%